2014
DOI: 10.1016/j.jor.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of plain radiographs in the classification of distal radius fractures

Abstract: Sensitivity of radiographs to classify Frykman or AO grades was 12.5%, indicating interpretation using plain radiographs alone is often inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…According to Küçük et al, 22 the classification systems for evaluating fractures of the distal extremity of the radius presented inconsistent results and they suggested that there was a need to create new classifications. In the study by Evans et al, 29 , 30 the sensitivity of radiographs for making classifications using the Frykman and AO systems was only 12.5%. These authors stated that evaluations using radiographs alone were insufficient and suggested that there was a need for other types of examinations in order to increase the reliability and reproducibility, as we found in the presented study, in which we achieved good concordance using the universal and AO classification systems.…”
Section: Discussionmentioning
confidence: 94%
“…According to Küçük et al, 22 the classification systems for evaluating fractures of the distal extremity of the radius presented inconsistent results and they suggested that there was a need to create new classifications. In the study by Evans et al, 29 , 30 the sensitivity of radiographs for making classifications using the Frykman and AO systems was only 12.5%. These authors stated that evaluations using radiographs alone were insufficient and suggested that there was a need for other types of examinations in order to increase the reliability and reproducibility, as we found in the presented study, in which we achieved good concordance using the universal and AO classification systems.…”
Section: Discussionmentioning
confidence: 94%
“…First, this is a retrospective study, which has its drawbacks such as selection bias and limited clinical data. Second, due to lack of a very good or excellent inter- and intra-observer reproducibility in the existing classifications of distal radius fractures [23], AO subclassifications based on X-ray and/or CT scans may also have inconsistencies, leading to changes in our conclusion. Ma et al described that X-ray results might be false negative in diagnosis of die-punch fracture.…”
Section: Discussionmentioning
confidence: 98%
“…1 Organizing fractures into widely recognized classifications is important for determining and planning treatment options. 2 A number of authors have attempted to simplify the current classification systems available, despite the challenges of obtaining excellent reliability, guaranteeing ideal treatment and predicting prognoses. 3 …”
Section: Introductionmentioning
confidence: 99%